Pengaruh Good Corporate Governance dan Ukuran Perusahaan Terhadap Kinerja Keuangan Perusahaan Pertambangan yang Terdaftar di BEI Periode 2021-2023 - Ramadani, Mutiara Dwi (Asosiasi Dosen Akuntansi Indonesia, 2025)
This study aims to determine the influence of the board of directors, audit committee, and company size on the financial performance of mining companies listed on the IDX for the 2021-2023 period. The method used is a quantitative approach with multiple linear regression analysis. The research population includes mining companies listed on the IDX with a purposive sampling technique. The result of the study shows that individually, the board of directors and the audit committee have no influence on the company’s financial performance. In contrast, company size has a negative influence on financial performance. Overall, the board of directors, audit committee, and the size of the company have no effect on the company’s financial performance.